2014
DOI: 10.1128/iai.01236-13
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Type IV Secretion-Dependent Recruitment of Macrophage Autophagosomes

Abstract: cCoxiella burnetii is an intracellular Gram-negative bacterium that causes human Q fever, a flu-like disease that can progress to chronic, life-threatening endocarditis. In humans, C. burnetii infects alveolar macrophages and promotes phagosomal fusion with autophagosomes and lysosomes, establishing a unique parasitophorous vacuole (PV) in which to replicate. The pathogen uses a Dot/Icm type IV secretion system (T4SS) to deliver effector proteins to the host cytoplasm, where they alter cellular processes to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
77
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 43 publications
13
77
0
2
Order By: Relevance
“…Cell lysates were collected for SDS-PAGE analysis at 72 h post-infection. In agreement with previous studies [26], there was a lack of SQSTM1 degradation during infection with WT Coxiella . In fact, SQSTM1 levels were increased under these conditions, but could be rescued with starvation (Figure 5(e)).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Cell lysates were collected for SDS-PAGE analysis at 72 h post-infection. In agreement with previous studies [26], there was a lack of SQSTM1 degradation during infection with WT Coxiella . In fact, SQSTM1 levels were increased under these conditions, but could be rescued with starvation (Figure 5(e)).…”
Section: Resultssupporting
confidence: 93%
“…Increasing amounts of lipidated LC3B were observed at 48 and 72 h post-infection. Thus, in agreement with previous literature [26], it was observed that LC3B-I to LC3B-II conversion occurs specifically in response to Coxiella infection (Figure 5(a)).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations